2012
DOI: 10.1002/eji.201242526
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin‐27 by human neutrophils regulates their function during bacterial infection

Abstract: Septicemia is the most severe form of melioidosis caused by the Gram-negative bacterium, Burkholderia pseudomallei. Here, we showed that levels of IL-27p28 transcript and protein were both significantly elevated in patients with sepsis, particularly melioidosis and in patients with unfavorable disease outcome. Moreover, monocytes/macrophages and neutrophils were the major source of IL-27 during infection. Addition of exogenous IL-27 in vitro resulted in significantly increased bacterial survival, reduced B. ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…In accordance with the above mentioned dual role of IL-27 in Leishmania infection are our in vivo results, which show augmented parasite loads due to IL-27 treatment, while the lesion sizes were comparable in both groups after the fourth week of infection. Interestingly, a recent report showed that IL-27 enhanced the survival of the Gram-negative bacterium Burkholderia pseudomallei by depressing microbicidal cellular mechanisms (Rinchai et al, 2012). This underlies, together with our findings, the possible significant ability of IL-27 to modulate infections caused by a diversity of different pathogens.…”
Section: G Modelsupporting
confidence: 70%
“…In accordance with the above mentioned dual role of IL-27 in Leishmania infection are our in vivo results, which show augmented parasite loads due to IL-27 treatment, while the lesion sizes were comparable in both groups after the fourth week of infection. Interestingly, a recent report showed that IL-27 enhanced the survival of the Gram-negative bacterium Burkholderia pseudomallei by depressing microbicidal cellular mechanisms (Rinchai et al, 2012). This underlies, together with our findings, the possible significant ability of IL-27 to modulate infections caused by a diversity of different pathogens.…”
Section: G Modelsupporting
confidence: 70%
“…IL-27 has been identified as a vital modulator of immune responses in T cells,12 14 15 and it also regulates biological functions of other immune effector cells, such as macrophages and neurtophils 13 16 17…”
Section: Introductionmentioning
confidence: 99%
“…This observation was supported by our finding in vitro of greater PD-L1 expression on PMNs after coculture with PBMCs than PMNs alone, where IFN-g is produced and secreted by T cells in response to polyclonal activator. We have shown that IL-27 could be produced by PMNs during bacterial infection (35), and IL-27 priming of naive T cells upregulated expression of PD-L1 (36), suggesting that IL-27 from B. pseudomallei-infected PMNs may also contribute to PD-L1 expression on PMNs.…”
Section: Discussionmentioning
confidence: 88%